2001
DOI: 10.1111/1468-2338.00193
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatism and Compliance: Employer Responses to the Working Time Regulations

Abstract: Analysis of Working Time Regulations data reveals three patterns of response that help to explain the lack of employers' post-implementation protest: coincidence with current practice; easy 'escape' options; and non-compliance. Whether this represents a failure of health and safety legislation or a pragmatic response to labour market conditions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research reported by the European Foundation for the Improvement of Living and Working Conditions (2001a) found that the Working Time Regulations 1998 which implemented a maximum 48-hour working week, has had limited impact on working hours. This was largely due to the use of the 'opt-out' clause by employers (Goss and Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Research reported by the European Foundation for the Improvement of Living and Working Conditions (2001a) found that the Working Time Regulations 1998 which implemented a maximum 48-hour working week, has had limited impact on working hours. This was largely due to the use of the 'opt-out' clause by employers (Goss and Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In‐built ‘flexibilities’, especially the individual opt‐out from the statutory average maximum working week, limited the impact of the Regulations. Goss and Adam‐Smith (2001) identified three patterns of response that help explain employer accommodation to the legislation: coincidence with current practice; easy ‘escape’ options; and non‐compliance. Nevertheless, the Working Time Regulations continue to be widely criticised by employers.…”
Section: Impact Of the Legislationmentioning
confidence: 99%